Glycine leaching of Sarcheshmeh chalcopyrite concentrate at high pulp densities in a stirred tank reactor. (1st October 2020) - Khezri, Maryam; Rezai, Bahram; Akbar Abdollahzadeh, Ali; Molaeinasab, Mehdi; Wilson, Benjamin P.; Lundström, Mari
Graphical abstract: Highlights: Glycine leaching of a chalcopyrite concentrate was studied at high pulp densities. Copper extractions were declined at high levels of pulp density and temperature. The process was controlled by the diffusion of reagents through the product layer. The activation energy of glycine leaching for the copper concentrate was 37.4 KJ/mol. Abstract: The simplest amino acid, glycine has recently been reported as a safe and environmentally benign reagent for the extraction of copper from both oxide and sulfide minerals. In the current study, leaching of a chalcopyrite concentrate from the Sarcheshmeh Copper Mine (Kerman, Iran) was conducted in stirred tank reactors in the presence of a glycine medium. The effect of some critical leaching parameters including glycine concentration (0.4–2 M), temperature (30–90 °C), stirring rate (250–750 rpm), pH (9–12), oxygen flowrate (0.5–2 L/min) and pulp density (1–20%) was investigated on copper recovery from the chalcopyrite concentrate. Results show that an increase in temperature from 30 to 60 ˚C enhanced the copper extraction, whereas at conditions > 60 ˚C a decrease in copper extraction was observed, probably as a result of the conversion of glycine to glycinate and decrease in oxygen solubility. Moreover, prolonged leaching times at higher pH levels (10.5 and 12) led to a decrease in the extraction of copper, primarily due to the chemical precipitation of copper sulfide and crystallization of copper glycinate. By increasing the pulp density from 1 to 20%, copper extraction declined significantly primarily as a consequence of the partial dissolved copper precipitation at higher copper concentrations. SEM/WDX analyses were subsequently used in order to evaluate the leach residues. Further investigation determined that the activation energy of the glycine leaching of concentrate was 37.4 KJ/mol, thus the kinetics were controlled by diffusion of the reagents through the product layer. From these results, it is evident that due to the high initial rate of glycine leaching and the precipitation of copper-bearing phases (i.e. copper glycinate and covellite) at high pulp densities, glycine leaching processes are recommended for the treatment of low grade chalcopyrite concentrates, ores or tailings.